Insulin Resistance Predicts Postoperative Cognitive Dysfunction in Elderly Gastrointestinal Patients - He, Xi; Long, Ge; Quan, Chengxuan; Zhang, Bin; Chen, Jia; Ouyang, Wen (Frontiers in Aging Neuroscience, 2019)
Background Members of the aging population who undergo surgery are at risk of postoperative cognitive dysfunction (POCD). Exploring an effective and reliable early predictor of POCD is essential to the identification of high-risk patients and to making prospective decisions. The purpose of this study was to examine whether preoperative insulin resistance is an independent predictor of POCD. Methods A total of 124 patients aged 60 years and older and who were scheduled for gastrointestinal surgery were enrolled in a prospective observational clinical study. All participants completed a battery of neuropsychological tests before surgery and 7 days later. POCD was defined as a decline of at least 1.5 SD on two or more of neuropsychological tests. Plasma concentration of the tumor necrosis factor α (TNF-α), C-reactive protein (CRP), and S-100β protein were measured. The status of insulin resistance was assessed by Homeostasis Model Assessment–Insulin Resistance (HOMA-IR). The relationship between HOMA-IR and POCD was assessed by Multivariable logistic regression models and the receiver operating characteristic (ROC) curve. Results Fifty one patients (41.1%) were diagnosed with POCD at 7 days after surgery. Preoperative HOMA-IR values of the POCD group were significantly higher than the non-POCD group. Furthermore, CRP and TNF-α levels of the POCD group were significantly higher at each postoperative time point (P < 0.05). The preoperative HOMA-IR value was an independent predictor of POCD (adjusted OR 1.88, 95% CI, 1.18–2.99) even after adjust for confounding variables, and when dichotomized, individuals above the HOMA-IR threshold (HOMA-IR > 2.6) had a three-times higher risk of POCD (OR 3.26; 95% CI, 1.07–9.91) compared to individuals below the threshold. The areas under the ROC curve of HOMA-IR was 0.804 (95% CI, 0.725–0.883; P < 0.001). The optimal cut-off value was found to be 0.583, with a sensitivity of 84.3% and specificity of 74%. The HOMA-IR value was positively associated with the TNF-α concentration at baseline (R2 = 0.43, P < 0.01) and 1 day after surgery (R2 = 0.3861, P < 0.01). Conclusion Preoperative insulin resistance is an effective predictor for the occurrence of POCD. Targeted prevention and treatment strategies of insulin resistance may be effective interventions of patients at risk for POCD.